A prospective study on the usefulness of high-resolution intraoperative infrared thermography in intracranial tumors - Menezes, Diego Rodrigues; de Lima, Lázaro; Mansilla, Raíssa; Conci, Aura; Rueda, Fernanda; Velarde, Luis Guilhermo Coca; Landeiro, José Alberto; Acioly, Marcus André (Frontiers in Surgery, 2024)
technique with potential application in different areas of neurosurgery. Despite technological advances in the field, intraoperative IT (IIT) has been an underestimated tool with scarce reports on its usefulness during intracranial tumor resection. We aimed to evaluate the usefulness of high-resolution IIT with static and dynamic thermographic maps for transdural lesion localization, and diagnosis, to assess the extent of resection, and the occurrence of perioperative acute ischemia.Methods: In a prospective study, 15 patients affected by intracranial tumors (six gliomas, four meningiomas, and five brain metastases) were examined with a highresolution thermographic camera after craniotomy, after dural opening, and at the end of tumor resection.Results: Tumors were transdurally located with 93.3% sensitivity and 100% specificity (p <0.00001), as well as cortical arteries and veins. Gliomas were consistently hypothermic, while metastases and meningiomas exhibited highly variable thermographic maps on static (p = 0.055) and dynamic (p = 0.015) imaging.Residual tumors revealed non-specific static but characteristic dynamic thermographic maps. Ischemic injuries were significantly hypothermic (p <0.001).High-resolution IIT is a non-invasive alternative intraoperative imaging method for lesion localization, diagnosis, assessing the extent of tumor resection, and identifying acute ischemia changes with static and dynamic thermographic maps.